Posterior tracheal wall leading to life-threatening obstruction of tracheostomy tube - Sanjay Singhal (Thieme Medical and Scientific Publishers Pvt. Ltd., 2013)
This is a case report of a 28-year-old male patient with severe traumatic brain injury and Glasgow coma scale score = 8: E2 M5 V T , who required a tracheotomy for airway protection. On day 5, a surgical tracheotomy was performed with size 8 tracheotomy tube (TT). On the 4 th day of post-tracheostomy, he developed a sudden onset respiratory distress while on T-piece. Immediate fiber optic bronchoscopy revealed almost a complete closure of TT due to posterior tracheal wall indrawing into the TT with every inspiratory effort.